2009
DOI: 10.1007/s11336-009-9115-2
|View full text |Cite|
|
Sign up to set email alerts
|

Exemplar-Based Clustering via Simulated Annealing

Abstract: cluster analysis, partitioning, heuristics, p-median model, simulated annealing,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 57 publications
2
27
0
Order By: Relevance
“…Brusco and Köhn () showed that the affinity propagation algorithm often failed to obtain a globally optimal solution even for relatively small problem instances from the literature. Similar findings have been reported by Brusco and Köhn () and Brusco and Steinley (). Nevertheless, it should be acknowledged that suboptimality issues have commonly plagued traditional methods such as Ward's method and K ‐means clustering (Brusco & Cradit, ; Brusco & Steinley, ; Steinley, , ), yet such methods have been gainfully employed for several decades.…”
Section: Merits Of Affinity Propagation For Psychological Researchsupporting
confidence: 92%
See 2 more Smart Citations
“…Brusco and Köhn () showed that the affinity propagation algorithm often failed to obtain a globally optimal solution even for relatively small problem instances from the literature. Similar findings have been reported by Brusco and Köhn () and Brusco and Steinley (). Nevertheless, it should be acknowledged that suboptimality issues have commonly plagued traditional methods such as Ward's method and K ‐means clustering (Brusco & Cradit, ; Brusco & Steinley, ; Steinley, , ), yet such methods have been gainfully employed for several decades.…”
Section: Merits Of Affinity Propagation For Psychological Researchsupporting
confidence: 92%
“…Brusco and Köhn () showed that the number of clusters could vary drastically (from just a few clusters to several hundred) as the preference values were changed. More recently, Brusco and Steinley () conducted a simulation‐based evaluation of different multiples of the median for setting the preference vector.…”
Section: Underlying Optimization Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, multiple restarts of the algorithm are advised. Hansen and Mladenović (1997) indicated that the multiple restart approach was generally effective for problems where K < 50 (see also Brusco & Köhn. 2009).…”
Section: Methodsmentioning
confidence: 99%
“…To select an optimal number of clusters, we performed visual analysis of a dendrogram representing the structure of the data and confirmed that we could identify natural groupings using bivariate matrices which provided construct validation. Next, we used the k-medians cluster methodology with a Euclidean distance similarity measure (L2) to verify cluster classifications, for a set number of k clusters ranging from 3–8 (Brusco & Köhn, 2009; Kohn et al, 2010). We used the Calinski pseudo-F statistic, which measures the ratio of between cluster variance to within cluster variance as a quantitative measure of the distinctness of the groups generated by the cluster analysis and provide a stopping rule to optimize the number of groups selected (Calinski & Harabasz, 1974).…”
Section: Methodsmentioning
confidence: 99%